United States : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2007)
The size and sources of international spillovers of activity remain subject to significant uncertainty. This Selected Issues paper uses a new approach to differentiating these effects using disturbances to a diverse group of small industrial countries as a proxy for global shocks. The results from the baseline vector autoregressions suggest that shocks to the United States are significant for foreign activity. The paper also evaluates alternative explanations for the easy financing of the U.S. current account deficit in recent years.